What is peculiar to human beings is not reason but free volition - Martínez-Freire, Pasual F. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
My claim is that human beings are rational agents but they can not be defined as the rational agents. Cognitive sciences (psychology and neuroscience, and also artificial intelligence) tell us that some animals and some machines are rational agents as well. In my opinion the most characteristic feature of women and men is not their rational dimension but their volitional dimension, that is, their aspect of being free agents. It is precisely in this volitional aspect where we find the mental processes that very likely are non-physical (and perhaps spiritual).